Altre voci dell’Oltremare: una lettura intersezionale dei romanzi coloniali di Mura e Pina Ballario (Comparatismi, 2025)
In the Italian context, the colonial novel has been the subject of limited critical investigation, and even more underexplored is the colonial literary production by women writers. Focusing on the case studies of Sambadù, amore negro by Mura and Fortuna sottovento by Pina Ballario, this article analyzes the Italian colonial novel through an intersectional methodology. This perspective aims, on the one hand, at examining how gender and racial identities are shaped precisely through the simultaneous intersection of gender and race, and on the other, at exploring the racial imaginary that the authors drew upon and often reproduced.
Keywords: Colonial novel; Italian colonialism; Mura; Pina Ballario; Intersectionality